Wedding Organizer Goods And Services Rental System : Case Study: Dina Griya Rias - Putra, Didik Sukma; Aji, Adam Sekti (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The problem faced by Dina Griya Rias as a wedding organizer service provider is the use of a manual rental system, such as handwritten records, face-to-face communication, and phone calls. This manual process often causes issues like scheduling errors, delayed order confirmations, difficulty monitoring item availability, and limited access to fast and accurate information. Without a digital system, operational efficiency and service quality will remain hindered, reducing customer satisfaction and business competitiveness. This study aims to design and develop a web- and mobile-based rental system for wedding goods and services that can be used by both admins and customers. The system includes real-time item availability monitoring, rental transaction recording, and online booking accessible anytime. Early results show that the system improves rental management efficiency, reduces human error, and provides faster and more convenient services for customers and administrators.